2007
DOI: 10.3346/jkms.2007.22.s.s79
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Aspects of 542 Cases of Pancreatic Cancer: a Special Emphasis on Small Pancreatic Cancer

Abstract: Small pancreatic cancers (longest diameter ≤2 cm) have been regarded as preliminary to early pancreatic cancer, which was thought to be highly curable. During our experience since 1989, we evaluated 542 cases of pancreatic cancer. Among them we found 74 cases of tumors ≤2 cm in diameter, small pancreatic cancer (TS1 pancreatic cancer). Well-differentiated adenocarcinomas (18.9%) and absence of symptoms (8.1%) were more frequent in patients with TS1 than in those with larger pancreatic tumors. Only 16 of the 74… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…The early pathogenesis of pancreatic cancer is incompletely understood as early tumours are so rarely found. As more small tumours are resected, tissue analysis should lead to the elucidation of the stepwise intracellular changes as tumours develop [33] . The screened population can also provide a bank of clinical samples, these could include blood, urine, saliva and possibly pancreatic juice; these samples can be used retrospectively to test novel molecular screening modalities.…”
Section: Scientific Benefits Of Secondary Screeningmentioning
confidence: 99%
“…The early pathogenesis of pancreatic cancer is incompletely understood as early tumours are so rarely found. As more small tumours are resected, tissue analysis should lead to the elucidation of the stepwise intracellular changes as tumours develop [33] . The screened population can also provide a bank of clinical samples, these could include blood, urine, saliva and possibly pancreatic juice; these samples can be used retrospectively to test novel molecular screening modalities.…”
Section: Scientific Benefits Of Secondary Screeningmentioning
confidence: 99%
“…9,10 Much of the research on ''small'' pancreatic cancers has been conducted in Asia, mainly Japan. [11][12][13][14][15][16] Most studies defined small pancreatic cancers as those\2 cm in size, but a few investigated those sized 1 cm and smaller. [11][12][13][14][15][16] To date, no comparable western population studies have specifically investigated the demographics, incidence, and outcomes among patients with ''small'' pancreatic cancers.…”
mentioning
confidence: 99%
“…However, small IDCs that measure less than 2 cm in diameter are associated with a significantly more favorable prognosis than larger IDCs [1][2][3]. The clinicopathological features of small IDCs have been extensively studied [3,9], but the effects of the site of tumor origin in the pancreatic duct on these features have not been described.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, the treatment outcomes for IDC are poor. Interestingly, studies have indicated that patients with IDCs measuring less than 2 cm in diameter have a significantly better prognosis than patients with larger IDCs [1][2][3]. Therefore, the treatment outcome in patients with IDCs may be improved by early tumor detection, which requires an understanding of the characteristics and progression of small IDCs.…”
Section: Introductionmentioning
confidence: 97%